THE SCIENCE PROCESS SKILL DIVERFICATION OF SUBJECT SPECIFIC PEDAGOGY BASED ON PROJECT BASED LEARNING - Rahayu, Wiworo Retnadi Rias (Universitas Djuanda, 2016)
Curriculum 2013 to emphasize of learning result on cognitive, affective, and skill. Curriculum 2013 not only to emphasize cognitive, however, also affective and skill need to be developed in the learning process. One of the skills that should be developed is the scientific process skills, because it is the high learning result. The objectives of this research are to know the science process skill diversification. Procedure this research using experiment method to design of Nonequivalent Control-Group Pretest Posttest Design. The results of this research there are the science process skills diverse using SSP of science based on PjBL and using teacher’s SSP.